2017
DOI: 10.1016/j.stemcr.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Stage of Adult Human Stem Cell-Derived Retinal Pigment Epithelium Cells Influences Transplant Efficacy for Vision Rescue

Abstract: SummaryAge-related macular degeneration (AMD) is a common cause of central visual loss in the elderly. Retinal pigment epithelial (RPE) cell loss occurs early in the course of AMD and RPE cell transplantation holds promise to slow disease progression. We report that subretinal transplantation of RPE stem cell (RPESC)-derived RPE cells (RPESC-RPE) preserved vision in a rat model of RPE cell dysfunction. Importantly, the stage of differentiation that RPESC-RPE acquired prior to transplantation influenced the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 30 publications
(49 reference statements)
1
64
0
1
Order By: Relevance
“…and additional statistics data (individual Hedges' g, lower-and upper limits) can be found in Table S6. Sixteen studies [26][27][28]31,[34][35][36][37][38][39][41][42][43][46][47][48] reporting 96 experiments were included in the meta-analysis. Ninety-one studies were performed in rats and five in mice.…”
Section: Behavioral Assaysmentioning
confidence: 99%
“…and additional statistics data (individual Hedges' g, lower-and upper limits) can be found in Table S6. Sixteen studies [26][27][28]31,[34][35][36][37][38][39][41][42][43][46][47][48] reporting 96 experiments were included in the meta-analysis. Ninety-one studies were performed in rats and five in mice.…”
Section: Behavioral Assaysmentioning
confidence: 99%
“…25,26 In the early stages of age-related macular degeneration, before photoreceptors are fully lost, dysfunctional RPE has been replaced and sight restored in animals by transplanting new RPE cells into the macula. 27 At later stages of age-related macular degeneration, cell therapy would require the transplantation of photoreceptor cells (or cells that could differentiate into photoreceptor cells), in addition to the RPE cells.…”
Section: The E Y Ementioning
confidence: 99%
“…They are also prone to tumour formation and immune rejection (Lee, Tang, Rao, Irving, & Wu, ; Xian & Huang, ) and therefore could potentially cause safety and long‐term cell survival concerns (Carr et al, ; Diniz et al, ; Lu et al, ; Nakano‐Okuno, Borah, & Nakano, ; Westenskow et al, ). A newer source of human RPE cell is the adult RPESCs, which are not tumorigenic (Salero et al, ) and show great potential to preserve vision based on preclinical studies (Blenkinsop et al, ; Davis et al, ; Davis et al, ; Stanzel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Following, it was shown that subretinal injection of a suspension of RPESC‐RPE cells is efficacious at preventing vision loss in the Royal College of Surgeons rat model of retinal degeneration (Davis et al, ). Notably, a particular intermediate stage of the RPESC‐RPE cell product was found to be most efficacious at preserving vision in this model (Davis et al, ).…”
Section: Introductionmentioning
confidence: 87%